Developing brand ambassadors: the role of brand-centred human resource management - Alshuaibi, Ahmad Said; Mohd Shamsudin, Faridahwati; Abd Aziz, Norzalita (2016)
In this paper, we propose the role of brand centered human resource management (HRM) in supporting the internal branding initiative toward the development of brand ambassadors in organizations.By brand ambassadors, we mean employees who are not necessarily involved in sales or marketing job, but who are also partly responsible for the promotion of the organization brand to external stakeholders, such as customers. Because the brand ambassadors are expected to live the brand and project the correct image of the company brand, it is vital that they understand and accept the brand value proposition. In order to help them do their job well in delivering the brand promise, it is essential that brand-centered HRM is instituted.Brand-centered HRM refers to the HR-related practices, such as hiring, training and development, performance appraisal, and compensation, to name a few, that are implemented to make employees produce positive attitude and behaviors toward the brands of the firm (Chiang et al., 2012).When the employees are able to play the role of good brand ambassadors to the external customers, it is expected that customers’ brand experience will be enhanced, resulting in customer brand loyalty.In essence, brand-centered HRM is key toward the accomplishment of brand success and survival in the marketplace as the external branding and internal branding strategies are aligned.